(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Union Territory of Jammu and Kashmir, with its historical intricacies and geopolitical significance, serves as a microcosm for studying decentralized governance in the broader context of India’s political evolution. This research critically examines the role played by local institutions, such as Panchayats and Municipalities, in shaping the political trajectory of the region and its implications for the natioun. Utilizing a multifaceted methodology that includes interviews, surveys, and document analysis, the study delves into the historical context of governance in Jammu and Kashmir, assessing pre- and post-independence structures. The analysis of current local governance mechanisms explores the functioning, powers, and challenges faced by these institutions. Addressing administrative complexities and political tensions, the research identifies both challenges and opportunities for socioeconomic development at the local level. The study investigates the impact of decentralized governance on broader themes such as political stability, integration, and representation, contributing insights that extend beyond the specific region to inform discussions on India’s overall political landscape. In conclusion, the research offers policy recommendations to enhance the effectiveness of decentralized governance in the Union Territory, fostering a more inclusive and participatory political evolution in line with the diverse needs of the local populace.